Interleukin-6 extraction ratios during prolonged CytoSorb hemoadsorption depend on procedural blood flow - Gubensek, Jakob; Vajdic Trampuz, Barbara; Zrimsek, Matej; Persic, Vanja (Frontiers in Medicine, 2025)
BackgroundHemoadsorption with CytoSorb is a novel treatment for cytokine release syndrome, but there are few published data on the rate of cytokine removal with prolonged use. Here, we report a prospective observational study of IL-6 extraction ratios with prolonged CytoSorb use.MethodsA secondary analysis was conducted on a prospective observational cohort study involving patients treated with CytoSorb. Blood samples for IL-6 were taken before treatment, after 30 min, and every 6 h of treatment at three sites: (1) before the adsorber, (2) between the adsorber and dialyzer, and (3) after the dialyzer. The extraction ratios of the adsorber were then calculated.ResultsWe included 21 dialysis circuits performed in 15 critically ill patients, mainly those with cytokine storm because of septic shock. The median extraction ratio of IL-6 after 30 min was 26% (interquartile range, IQR 18–37%). The ratio decreased to 10% (6–21%) after 6 h and remained between 9–16% for up to 24 h (with a low number of circuits used beyond 12 h). Extraction ratios were similar in circuits with high (>1,000 ng/L) and low baseline IL-6 levels. On the contrary, in circuits with high blood flow (≥200 mL/min, i.e., intermittent hemodialysis), the extraction ratio was very low (median 6%) at 6 h and negligible thereafter, whereas the circuits with lower blood flow (<200 mL/min) maintained an extraction ratio of 20% for up to 12 h.ConclusionWe observed a significant reduction in the IL-6 extraction ratio within 6 h in circuits with high blood flow, whereas circuits with lower blood flow maintained an adequate extraction ratio for up to 12 h. Recent consensus recommendations on an 8–12 h exchange interval should mainly be applied to continuous dialysis methods, whereas in intermittent hemodialysis, the exchanges should be more frequent.